Trade Openness and Digital Technologies in African and Non- African Countries - (:unkn) unknown (My University, 2024)
Aims: The main objective of this paper is to examine whether digital technologies explain the differences in the achievement of trade openness between Africa and other parts of the world. Methodology: Using OLS and two-stage instrumental variables (IV-2SLS) methods with data from 117 countries. Results: Sub-Saharan African countries are less advanced in terms of trade openness than the rest of the sub-region (South Asia; North America; Latin America and the Caribbean; East Asia and the Pacific; and the Middle East and North Africa). In fact, imports of digital tools into African countries are still low due to customs duties on these products. the low use of ICT tools in African countries can be explained by subscription costs (internet), which remain very high in the region compared to developed countries. Conclusion: African countries speed up the digital transformation of their economies, such as the digitization of information and customs procedures. It would also be a good idea to speed up the roll-out of fiber optics and improve access to electricity to connect people and cities in African countries, which would considerably reduce the cost of doing business on the continent.
Keywords: African Research